2007
DOI: 10.1007/s00702-007-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

Color perception deficits in co-existing attention-deficit/hyperactivity disorder and chronic tic disorders

Abstract: Summary. Preliminary findings suggest that color perception, particularly of blue-yellow stimuli, is impaired in attention-deficit=hyperactivity disorder (ADHD) as well as in chronic tic disorders (CTD). However, these findings have been not replicated and it is unclear what these deficits mean for the comorbidity of ADHD þ CTD.Four groups (ADHD, CTD, ADHD þ CTD, controls) of children with similar age, IQ and gender distribution were investigated with the Farnsworth-Munsell 100 Hue Test (FMT) and the Stroop-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 47 publications
(36 reference statements)
4
42
3
1
Order By: Relevance
“…The questionnaire didn't explicitly ask for color perception deficits, however, such deficits seem not to degrade performance on word-color interference tasks. 29,30 The questionnaire also didn't ask for cognitive deficits: we deemed all subjects to be free of such deficits since they lived independently in the community, arrived without assistance in the correct room at the correct time, and followed our instructions properly. None of the subjects had participated in research on gait or cognition within the preceding six months.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire didn't explicitly ask for color perception deficits, however, such deficits seem not to degrade performance on word-color interference tasks. 29,30 The questionnaire also didn't ask for cognitive deficits: we deemed all subjects to be free of such deficits since they lived independently in the community, arrived without assistance in the correct room at the correct time, and followed our instructions properly. None of the subjects had participated in research on gait or cognition within the preceding six months.…”
Section: Methodsmentioning
confidence: 99%
“…As previous research has stated, RAN/RAS naming tasks are closely related to variables involved in reading and writing processes (Arnell et al, 2009;Georgiu et al, 2009;Gasperini, Brizzolara, Cristofani, Casalini, & Chilosi, 2014) and attentional processes (Roessner et al, 2008;Stringer, Toplak, & Stanovich, 2004). This may be because naming tasks activate a series of interrelated processes which need a specified time between them.…”
Section: Discussionmentioning
confidence: 73%
“…While the existing relationship between naming colours and ADHD is in line with previous research (Roessner et al, 2008), the same cannot be said of the relationship between the alphanumeric RAN and ADHD, as the majority of studies state that deficits in the alphanumeric RAN are related specifically to the presence of reading difficulties (Pham, Fine, & Semrud-Clikeman, 2011). This may be because those studies have been carried out in opaque languages like English, rather than transparent languages such as Spanish.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Merely one study reported deficits for adults with ADHD along the blue spectrum only, as indicated by a significant effect of medium size (d = 0.58; Kim et al 2014b). In contrast, children with ADHD appear to have deficits in hue discrimination, especially along the blue-yellow axis (as indicated by significant effects of large size; Cohen's d ranged from 1.06 to 1.23), but they also seem to have difficulties with color discrimination along the red-green axis, as shown by significant effects of medium to large size; Cohen's d ranged from 0.75 to 0.98 (Banaschewski et al 2006;Roessner et al 2008).…”
Section: Visual Perceptionmentioning
confidence: 99%